2020
DOI: 10.3390/ijerph17113966
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Work-to-Family Conflict and Self-Reported General Health among Working Parents in Germany

Abstract: The combination of work and family roles can lead to work-to-family conflict (WTFC), which may have consequences for the parents’ health. We examined the association between WTFC and self-reported general health among working parents in Germany over time. Data were drawn from wave 6 (2013) and wave 8 (2015) of the German family and relationship panel. It included working persons living together with at least one child in the household (791 mothers and 723 fathers). Using logistic regressions, we estimated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Obtained estimates of the test-retest reliabilities for the German version of the WFC & FWC Scale can be interpreted as being acceptable ( Nunnally and Bernstein, 1994 ; Vilagut, 2014 ) and exceed test-retest reliabilities reported for similar instruments assessing WFC or FWC ( Fisher et al, 2016 ; Min et al, 2021 ). Thus, the German-language version of the WFC & FWC Scale can be recommended for future longitudinal studies that analyze (systematic) changes in WFC or FWC over time ( Borgmann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtained estimates of the test-retest reliabilities for the German version of the WFC & FWC Scale can be interpreted as being acceptable ( Nunnally and Bernstein, 1994 ; Vilagut, 2014 ) and exceed test-retest reliabilities reported for similar instruments assessing WFC or FWC ( Fisher et al, 2016 ; Min et al, 2021 ). Thus, the German-language version of the WFC & FWC Scale can be recommended for future longitudinal studies that analyze (systematic) changes in WFC or FWC over time ( Borgmann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…FWC can be caused by family responsibilities setting time demands or causing strain that interfere with work responsiblities ( Greenhaus and Beutell, 1985 ; Netemeyer et al, 1996 ). The experience of strong WFC and/or strong FWC has been associated with negative work-related outcomes (such as lower job performance, reduced job satisfaction, or feelings of exhaustion), family related outcomes (e.g., reduced leisure satisfaction, more frequent conflicts with family members), or stress/health-related outcomes (e.g., heightened anxiety, depression, and poorer general health) ( Amstad et al, 2011 ; Sirgy and Lee, 2018 ; Borgmann et al, 2019 ; Borgmann et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of gender distinction, in 2007, Oramas et al [ 15 ] reported on a study conducted between 1997 and 1999 by Weber et al (2015), in which all 408 cases of early retirement in teachers were reviewed. In that study, 45% gave psychosomatic and psychiatric disorders as a cause, with a higher incidence occurring in women than in men, which is historically due to the double presence or work–family conflict among women [ 16 , 17 ]. This was the main gender difference identified between psychosocial risks in Chile after the SUSESO/ISTAS21 questionnaire in 2016, with an odds ratio (female/male) of 1.59, which decreased between 2017 and 2019, with values of 1.59, 1.09, and 1.02, respectively [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Work-family conflict (WFC) is considered as a predictor of health determinants, well-being, and organizational outcomes [ 3 , 4 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Findings in Germany show that WFC is correlated with personal burnout and behavioral and cognitive stress symptoms [ 4 , 34 ] and poor health [ 28 , 37 ]. For example, double-duty caregivers providing informal care to a family member in need are at high risk of developing symptoms of overload [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%